KEWENANGAN PARALEGAL BERDASARKAN UU NO. 16 TAHUN 2011 TENTANG BANTUAN HUKUM DI PERHIMPUNAN BANTUAN HUKUM DAN HAK ASASI MANUSIA INDONESIA SULAWESI SELATAN (PERSPEKTIF HUKUM ISLAM) - mustakim,; Halimah,; Alimuddin, (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
The establishment of paralegal authority in providing legal aid based on Law no. 16 of 2011 concerning legal aid at the Indonesian legal aid and human rights association, South Sulawesi, the purpose of this study is to determine the authority of paralegals according to law no. 16 of 2011 and its implementation in providing legal assistance to the community. Because it is not uncommon for errors to be made when handling a case without appropriate legal provisions or there are regulations that are violated in handling a case, this type of research is a qualitative descriptive research field. This study was conducted to collect a number of data obtained from field informants to find various facts or social phenomena, all of which analyzed and attempted to theorize based on what was observed. The location of the research was carried out, the office of the law and human rights association in South-Sulawesi. In carrying out the authority in providing legal aid, the community can get assistance and ensure that a fair law is created in handling a case and there is no violation of the law in the case process that often occurs in the community.